Analisis Keterampilan Berpikir Kritis Mahasiswa Melalui Model Blended-Project Based Learning Terintegrasi Keterampilan Abad 21 Berdasarkan Students Skill Level - Ani Purwanti; Noor Hujjatusnaini*; Nurul Septiana; Astuti Muh Amin; Jasiah Jasiah (Universitas Syiah Kuala, 2022)
Thinking ability is one of the skills that must be had by all people in facing the demands of the 21st century, namely critical thinking skills. This skill can be achieved by delivering the material more clear and objective. Thus, the purpose of this study is to know the effect of implementing blended PjBL integrated 21st century skills on students’ critical thinking skills. The sample of this study amounted to 39 students in the fifth semester of Biology Education at IAIN Palangka Raya with a non-equivalent control group design. The accumulation data of critical thinking skills was obtained by giving 20 items in the critical thinking domain in the form of pretest and posttest questions. The implementation of blended PjBL integrated 21st century skills is quite effective in the high-level class experimental class group, with the acquisition of N-gain = 56.75. This is reinforced by the results of hypothesis testing with the value of Sig. (2-tailed) = 0.000 0.05. It can be concluded that the implementation of blended PjBL integrated 21st century skills has a significant effect on students' critical thinking skills. The findings of this study is an alternative integrative model innovation between blended PjBL and 21st century skills-based on student skill level